Potential consequences of the international transfer of emission allowances under the updated national emissions targets by 2030 - Toshiki Tsutsui; Osamu Nishiura; Shinichiro Fujimori; Ken Oshiro (Global Environmental Change Advances)
All parties that signed the Paris Agreement are required to update their Nationally Determined Contributions (NDCs) every 5 years. The international transfer of emission allowances is a political instrument that has the potential to realize global emission reductions under the NDCs. This study conducted an economic assessment of the implementation of updated NDCs and quantified the effects of the international transfer of emission allowances using a global computable general equilibrium model. The results showed that updating NDCs increased gross domestic product (GDP) losses relative to the previous NDCs. The international transfer of emission allowances mitigated global GDP losses relative to baseline scenarios from 1.1 % to 0.7 % but there was an increase in some developing countries with relatively low emission reduction targets. While the international transfer of emission allowances could promote the reduction of global emissions in a cost-effective manner, it could also impose an economic burden on some developing countries through their linkages to the global carbon market. Thus, the results of this study indicate the importance of considering additional financial or technical support to developing countries.